Superhydrophobic Surface Modification On The Fabric Face Mask Materials - Thiyagu, Thanigesh (Universiti Sains Malaysia, 2018)
Disposable surgical masks and N95 respirators have resulted in environmental pollution. Subsequently resulted in increased demand in wearing fabric face mask which are washable, reusable, environmentally friendly and sustainable however, the limitation on fabric-based face mask is the chances for transmission of virus is higher due to the hydrophilic nature. To tackle the problem, the surface of the fabric is modified. Superhydrophobic surface with self – cleaning is proposed to tackle the issue. The present work investigates facile techniques for superhydrophobic coating on cotton, microfiber, and microfiber blend materials. Dip coating was employed to coat the coating solution on the fabric surface. The effect of concentration of HDTMS on the hydrophobicity of different fabrics were investigated. As the concentration of HDTMS increases, the hydrophobicity of the surface also increased. All cotton fabric surface coated with 5 % (v/v), 10 % (v/v) and 20 % (v/v) HDTMS concentration exhibited water contact angle (WCA) more than 150° and able to reach superhydrophobic state. Modification through bilayer coating solution on the microfiber and microfiber blend surface was done to enhance superhydrophobicity. All bilayer coated microfiber surface has WCA of more than 150° while microfiber blend surface reached WCA near to the superhydrophobic range. Modified cotton and microfiber surface displayed excellent water repellence and WCA of more than 150°. The mechanical strength and stability of coating over time of the superhydrophobic cotton and microfiber surfaces have been evaluated. Modified cotton and microfiber displayed excellent self – cleaning and stain – resistant properties.